La recepción de Juan de Tesalónica en la obra de Germán de Constantinopla (Limes: Revista de Estudios Clásicos, 2023)
In the 6th century, the Byzantine emperor Maurice instituted the feast of the Assumption by decree, fixing it on August 15; from that moment on, the celebration with which Mary had been honored since the time of the primitive Church was explicitly associated with her death. Since at least two centuries before, there was an incredible proliferation of apocryphal texts linked to the “dormition” (κοίμησις) of the Virgin, of which around seventy are preserved, written in the most varied languages (Greek, Syriac, Coptic, Latin, among others) and that account for a diversity of stories of the same event. From the onset of the feast, theologians and Christian preachers, on the occasion of it, took up the narrative of the passage of Mary to heaven. Among them, the oldest testimony in the Greek language is that of Bishop John of Thessalonica, in the seventh century, on whom German of Constantinople was based shortly after to write three of his homilies.Within the framework of the diversity to which we alluded, this communication, based on a comparative analysis of both texts, proposes to establish the common features that they present, as well as those in which one and the other differ, or that only appear in one of the versions, also trying to determine the reasons that led both authors to make the choices they made. This contribution seeks to verify that theme and objective are interwoven in the homilies to achieve different effects.